Kemampuan Komunikasi Interpersonal dan Sosialisasi pada Siswa Sekolah Dasar - Hidayah, Ratna; Salimi, Moh (Edukasi: Jurnal Penelitian dan Artikel Pendidikan, 2024)
One of the factors that adheres to students' socialization skills is interpersonal communication. The purpose of this paper is to reveal the relationship between interpersonal communication skills and socialization skills in elementary school students. This study uses a quantitative approach. The source of data was obtained by elementary school students of cluster 1, Temon District, Kulon Progo Regency. The data collection instrument used is a psychological scale of interpersonal communication consisting of openness, empathy, support, positivity and equality as well as socialization skills consisting of social adjustment, social skills and social acceptance. The data analysis used in this study is canonical correlation analysis. The results of the study showed that there was a reciprocal relationship between interpersonal communication and socialization skills in elementary school students of Group 1, Temon Kulon Progo District.